Penerapan Tesi Gawa Telur (Terapi Okupasi Pasca Gangguan Jiwa Pembuatan Telur Asin) - Laeli Farkhah; Hamdi Hamdi; Rully Andika; Trimeilia, S; Resti Ikhda; Putri M S (Universitas Malahayati Lampung, 2026)
ABSTRACT Mental disorders have become a major focus of government attention. The number of mental disorder cases continues to increase each year. Data from the Ministry of Health (2018) show that approximately 400,000 people suffer from mental disorders, equivalent to 1.7 per 1,000 population. Central Java Province ranks third with a prevalence of mental disorders reaching 8.7%. The Tesi Gawa Telur Occupational Therapy aims to empower clients as an effort to optimize recovery, prevent relapse, support daily activities, and promote financial independence. This study aims to determine the outcomes of implementing Tesi Gawa Telur Occupational Therapy in preventing relapse among patients with mental disorders. This research employed a descriptive design using a case study approach involving seven respondents. Before the implementation of Tesi Gawa Telur Occupational Therapy, Ny. A, Ny. B, Ny. C, Ny. D, Tn. A, Tn. B, and Tn. C were categorized as having severe mental disorders. After receiving Tesi Gawa Telur Occupational Therapy for one week, consisting of three sessions per week with a duration of 1–2 hours over a six-month period, none of the patients experienced relapse. Tesi Gawa Telur Occupational Therapy can improve patients’ knowledge and skills in producing salted eggs and generate marketable products. This occupational therapy intervention can also prevent relapse in patients with mental disorders. Keywords: Mental Disorders, Tesi Gawa Telur Occupational Therapy, Relapse. ABSTRAK Gangguan jiwa saat ini menjadi fokus perhatian pemerintah. Kasus gangguan jiwa setiap tahunnya mengalami peningkatan. Data Kementrian Kesehatan (2018) menunjukkan penderita ganggguan jiwa mencapai 400.000 jiwa atau sebesar 1,7 per 1.000 jiwa. Provisi Jawa Tengah menduduki peringkat ke tiga dengan jumlah penderita gangguan jiwa sebesar 8.7%. Terapi Okupasi Tesi Gawa Telur bertujuan untuk pemberdayaan klien sebagai upaya optimalisasi recovery, mencegah kekambuhan, aktivitas harian, dan mandiri secara finansial. Tujuan: Mengetahui hasil implementasi penerapan terapi okupasi Tesi Gawa Telur untuk mencegah kekambuhan. Metode: Penelitian ini bersifat bersifat deskriptif dengan desain penelitian studi kasus berjumlah 7 responden. Temuan: Sebelum diberikan terapi okupasi Tesi Gawa Telur Ny.A, Ny.B, Ny.C, Ny.D Tn.A, Tn.B, dan Tn.C dalam kategori gangguan jiwa berat. Setelah diberikan terapi okupasi Tesi Gawa Telur satu minggu 3 sesi dengan durasi 1-2 jam selama enam bulan, pasien tidak kambuh. Implikasi: Terapi Okupasi Tesi Gawa Telur dapat meningkatkan pengetahuan dan keterampilan membuat telur asin serta menghasilkan produk layak jual. Terapi okupasi ini juga dapat mencegah kekambuhan pasien gangguan jiwa. Kata Kunci: Gangguan Jiwa, Terapi Okupasi Tesi Gawa Telur, Kekambuhan.